REAL ESTATE MARKET OF THE WESTERN REGION OF UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2020)
Introduction. Given the great importance of the real estate market in the functioning of the market economic system and the problems of development of the domestic real estate market, the study of state regulation of this segment of market relations in Ukraine is becoming increasingly important. Immovable property performs two important functions at the same time: the means of production and the object of personal consumption. As a means of production, real estate is used in the production of the vast majority of material goods and services. Real estate used for living, recreation, cultural leisure, etc., acts as an object of personal consumption. Thus, real estate is at the center of a complex intersection of various economic processes, private and public interests, administrative norms, and rules. These restrictions affect the functioning of the real estate market and form a special internal structure. The structure of the real estate market depends on both the level of organization of the market and the composition of the real estate itself.The purpose of the article. Show the evolution of the real estate market, as well as find out the concepts of "real estate", "real estate market" and who are the participants in the real estate market. Find out how the price of housing has changed in 2020, what is housing security and what is happening now in the real estate market.Results. The real estate market is a complex differentiated system that includes some groups of relations depending on the subjects present in them. At the same time, it performs some functions, together provide the most rational distribution of the real estate in society according to its needs. The evolution of the real estate market was shown and the basic concepts in this area were clarified. Housing prices in 2020 increased compared to 2019, but a significant decline in prices is projected due to the Covid-19 coronavirus pandemic. She also found out that housing security is the protection of residential complexes, and at what stages is the protection of housing and communal services. Thus, the state must play an active role in the formation of the real estate market and implement policies to create conditions for the development of the market environment. The state must take an active part in investment processes because investing in real estate is characterized by a high multiplier effect and provides economic growth.Conclusions. To increase the efficiency of the market structure, there is an objective need for systematic monitoring of real estate market trends, which allows, if necessary, to promptly adjust public policy. In the economic crisis, all actions of the authorities aimed at the development of the real estate market of Ukraine must take into account its close relationship with other segments of the market economy (commodity markets, capital market, labor market), because the development of the real estate market is impossible
Keywords: real estate, real estate market, sellers, buyers, notaries, intermediaries, market functioning, market conditions